In a glass Grimmly - Gidwitz, Adam; Grimm, Jacob, 1785-1863; Grimm, Wilhelm, 1786-1859; Andersen, H. C. (Hans Christian), 1805-1875 (Puffin Books, 2013)
Frog joins cousins Jack and Jill in leaving their own stories to seek a magic mirror, encountering such creatures as giants, mermaids, and goblins along the way. Based in part on fairy tales from the Brothers Grimm and Hans Christian Andersen.